Efficiency of Rice Farming in the Corporate Farming Model in Central Java - Iskandar, Muhammad Joni; Jamhari, Jamhari (Universitas Muhammadiyah Yogyakarta, 2020)
The corporate farming approach on rice is aimed to increase the production on fields with the constraints of limited land area. The present research was aimed to analyze the impact of the implementation of corporate farming on the production, efficiency and inefficiency of the law land farming. The study was determined purposively in farmersâ€™ group union â€œTani Mandiri Dalanganâ€ in Sukoharjo Regency, Central Java. Sampling of the respondents used a census method involving all members totaling 51 farmers over two growing seasons. Data were analyzed using the frontier stochastic production function Maximum Likelihood Estimation (MLE) method frontier computing program 4.1c. The results showed that the corporate farming of rice production was affected by land area, Urea fertilizer and NPK fertilizer. Technical, economical and allocative efficiency corporate farming of rice farming has not been efficient. Technical efficiency shows the lowest efficiency value due to the use of factors of production exceeding the recommended regional dosage. Socio-economic factors that significantly affected the technical inefficiency of the low land rice farming are education, family size and extension.